Clinical Course and Outcome of COVID-19 Patients in a Tertiary Care Hospital: A Retrospective Study - Rizwan Yusaf Aziz A; Kisan Khade; Swati Sonawane; Cherian Philemon; Hritika Sharma; Tanusri Tetarbe (Institute of Medico-legal Publications Pvt Ltd, 2022)
Introduction: COVID-19 the deadly virus, was declared a pandemic by WHO in March, 2020 because of itsvirulent nature. It has been a piece of work to understand the mechanism of action and the disease pathology ofthe virus, due to its novel origin. The quality of healthcare is seen to be severely degrading during these times. Thetwo different types of COVID tests that are commonly available in the facility are RTPCR and Rapid Antigen Testor RAT. These help to identify whether the person is infected with the virus or not. With the current managementbeing successful in majority of the cases, we should also consider strengthening the existing modalities.Objective: To find the prevalence of COVID-19 patients and study their clinical course and outcomeMaterial and methods: Data regarding covid-19 patients was collected on basis of demographic profile by usinggoogle foms questionnaire at Dr. D.Y. Patil Hospital, Navi Mumbai.Results: A total of 500 patients were included in the present study with male preponderance with 61.4%. 99%patients were tested COVID positive, 73.2% had a history of exposure to COVID patients, 80% had a positive travelhistory, 99% lab tests were positive. 50.4% duration of the treatment lasted for 7-14 days. 67.6% were treated inthe wards, whereas, the remaining 32.4% were treated in the ICU. 19.6% patients required mechanical ventilatorsupport. 51% patients required oxygen therapy. 80.2% did not require intubation. All the patients were onantibiotics, and majority of the patients, i.e. 99.8% were on immuno-boosters as well. Antivirals were administeredin 80.6%. 82.8% were discharged with a negative swab. Out of the 17.2% patients with positive swab, mortality wasseen in 6.2% patients. 3.4% patients were referred to different centers, while the treatment of the remaining 7.6%patients was continued for a longer period of time.Conclusion: A stepwise perspective of non-pharmaceutical interventions, screening and testing procedures,implementation and compliance to distancing, hygiene measures and use of masks at airports, railway stations,other public places with pragmatic testing and tracing are effective measures that can be implemented. Worldwide numerous clinical trials are taking place for the treatment and prevention of COVID-19. Although, there is a rapidcomprehensive expansion in regard to COVID-19 and few agents appear to be promising, there are no definitelyproven effective therapies at this time. Evaluation of several agents by Scientists and researchers are progressiveand commendable.